Asymmetrical proliferative pattern loss linked to cyclin D1 overexpression during malignant transformation of the lip epithelium - Garcia, N. G.; Gonzalez-Moles, M. A.; Ruiz-Avila, I.; Bravo, M.; Ramos-Garcia, P.; Minicucci, E. M. [UNESP]; Domingues, M. A. C. [UNESP]; Oliveira, D. T. (Wiley-Blackwell, 2016)
BackgroundThere is inadequate knowledge on the involvement of oncogenic mechanisms linked to the cyclin (CCND1) gene in lip squamous cell carcinoma (LSCC). ObjectiveThe aim of this study was to analyse the implication of cyclin D1 in the malignant transformation of lip lesions. MethodsWe immunohistochemically studied 45 actinic cheilitis cases (15 mild dysplasia, 15 moderate dysplasia, 15 severe dysplasia/carcinoma in situ), 30 LSCC cases with adjacent non-tumour epithelium and 15 normal oral epithelium samples for detection of cyclin D1, -catenin and Ki-67. ResultsCyclin D1 and Ki-67 expressions were significantly increased in the basal layer of premalignant epithelia and peripheral layers of tumour nests vs. controls. Premalignant epithelia had lost their asymmetrical proliferative pattern. ConclusionLip carcinogenesis was associated with loss of the asymmetrical proliferative pattern, a preventive mechanism against lip oncogenesis, and with cyclin D1 overexpression.